Additive-modified perovskite solar cell and preparation method thereof
Patent Information
- Application Number
- CN202311759979.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-20
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-12-20
AI Technical Summary
然而,粗糙和不均匀的宽带隙钙钛矿薄膜严重影响后续薄膜沉积的致密性,导致全钙钛矿叠层电池的填充因子较低,特别是在大面积器件中这一现象更为明显
[0036]本申请提供的技术方案带来的有益效果包括:
Smart Images

Figure CN117560941B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of solar cell technology, and in particular to an additive-modified perovskite solar cell and its preparation method. Background Technology
[0002] Metal halide perovskites have emerged as promising materials for next-generation photovoltaic cells due to their excellent photoelectric properties and low manufacturing costs. Recently, single-junction perovskite solar cells achieved a certified power conversion efficiency of 26.1%, approaching the level of commercial silicon solar cells (26.7%). The ability to tune the bandgap of perovskite materials between 1.2 eV and 3.0 eV gives all-perovskite tandem solar cells significant potential for further improvements in photoelectric conversion efficiency.
[0003] Therefore, wide-bandgap perovskite solar cells are crucial for achieving high-efficiency tandem solar cells. However, rough and inhomogeneous wide-bandgap perovskite films severely affect the compactness of subsequent film deposition, resulting in a low fill factor for all-perovskite tandem cells, especially in large-area devices.
[0004] Developing high-quality perovskite thin films is crucial for promoting the commercialization of tandem perovskite photovoltaics. High-quality perovskite crystalline thin films typically have large grain sizes.
[0005] How to improve the grain size of perovskite films and obtain high-quality, uniform perovskite films is an urgent problem to be solved for the reproducible manufacturing of large-area tandem solar cells. Summary of the Invention
[0006] This application provides an additive-modified perovskite solar cell and its preparation method, which increases the grain size of the perovskite thin film, reduces non-radiative recombination, and improves the uniformity of the perovskite thin film. More importantly, the uniform and smooth perovskite thin film is beneficial for manufacturing more efficient all-perovskite tandem solar cells.
[0007] In a first aspect, an additive-modified perovskite solar cell is provided, comprising a first conductive glass layer, a first hole transport layer, a wide-bandgap perovskite polycrystalline layer, a first electron transport layer, and a metal electrode layer stacked sequentially; wherein the wide-bandgap perovskite polycrystalline layer is doped with a modifier, the modifier including piracetam.
[0008] In some embodiments, the first conductive glass layer is fluorine-doped tin dioxide or indium-doped tin dioxide;
[0009] And / or, the first hole transport layer includes a lower hole layer and an upper hole layer located on the lower hole layer, wherein the lower hole layer uses NiOx, where x takes the value 2 or 3, and the upper hole layer uses Me-4PACz or 2PACz;
[0010] And / or, the first electron transport layer is made of fullerene or PCBM, or the first electron transport layer includes a lower transport layer and an upper transport layer located on the lower transport layer, wherein the lower transport layer is made of fullerene or PCBM, and the upper transport layer is made of bartoplin or atomically deposited tin dioxide.
[0011] In some embodiments, a second conductive glass layer, a second hole transport layer, a narrow bandgap perovskite polycrystalline layer, and a second electron transport layer are sequentially stacked between the first electron transport layer and the metal electrode layer.
[0012] In some embodiments, the second conductive glass layer is made of bartoplin or atomically deposited tin dioxide, or the second conductive glass layer includes a lower conductive glass layer and an upper conductive glass layer located on the lower conductive glass layer, wherein the lower conductive glass layer is made of atomically deposited tin dioxide and the upper conductive glass layer is made of nano-gold or indium-doped tin dioxide.
[0013] And / or, the second hole transport layer is made of poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) or NiOx, where x is 2 or 3;
[0014] And / or, the second electron transport layer is made of fullerene or PCBM, or the second electron transport layer includes a lower transport layer and an upper transport layer located on the lower transport layer, wherein the lower transport layer is made of fullerene or PCBM, and the upper transport layer is made of bartoplin or atomically deposited tin dioxide.
[0015] Secondly, a method for preparing a perovskite solar cell modified with additives as described above is provided, comprising the following steps:
[0016] A first hole transport layer, a wide-bandgap perovskite polycrystalline layer, a first electron transport layer, and a metal electrode layer are sequentially fabricated on a first conductive glass layer to obtain an additive-modified perovskite solar cell.
[0017] In some embodiments, the fabrication of the first hole transport layer specifically includes:
[0018] First, NiOx is mixed and stirred with the first solvent, then spin-coated onto the first conductive glass layer, and then subjected to the first annealing treatment to obtain the lower hole layer, where x takes the value of 2 or 3.
[0019] Then, Me-4PACz or 2PACz is mixed and stirred with the second solvent, then spin-coated onto the lower cavity layer, followed by a second annealing treatment to obtain the upper cavity layer.
[0020] In some embodiments, the concentration of NiOx after mixing with the first solvent is 10 mg / ml to 20 mg / ml;
[0021] And / or, the concentration of Me-4PACz or 2PACz after mixing with the second solvent is 0.3 mg / ml to 1 mg / ml;
[0022] And / or, the first solvent is deionized water or isopropanol;
[0023] And / or, the conditions for the first annealing treatment include: annealing at 110℃~180℃ for 15min~40min;
[0024] And / or, the spin coating speed is 3000 rpm to 4000 rpm, and the spin coating time is 25 s to 40 s;
[0025] And / or, the second solvent is ethanol or isopropanol;
[0026] And / or, the conditions for the second annealing treatment include: annealing at 100℃~120℃ for 5min~15min.
[0027] In some embodiments, the preparation of a wide-bandgap perovskite polycrystalline layer specifically includes:
[0028] Formamidin hydroiodide (FAI), cesium iodide (CsI), lead iodide (PbI2) and lead bromide (PbBr2) were mixed in N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), and then piracetam was added after stirring to form a perovskite precursor solution.
[0029] The perovskite precursor solution is spin-coated onto the first hole transport layer, and after heating, a wide-bandgap perovskite polycrystalline layer is formed.
[0030] In some embodiments, the perovskite precursor solution contains formamidin hydroiodide (FAI) at a concentration of 0.96 mol / L, cesium iodide (CsI) at a concentration of 0.24 mol / L, lead iodide (PbI2) at a concentration of 0.48 mol / L, lead bromide (PbBr2) at a concentration of 0.72 mol / L, and piracetam at a concentration of less than 5 mg / ml.
[0031] And / or, the volume ratio of DMF to DMSO is (3-4):1;
[0032] And / or, stir at 50℃~70℃;
[0033] And / or, the heating process after spin-coating the perovskite precursor solution includes: first annealing at 55℃~75℃ for 90s~120s, and then annealing at 95℃~105℃ for 10min~15min.
[0034] In some embodiments, the fabrication of the first electron transport layer specifically includes: using a vacuum thermal evaporation method, firstly... A 20nm-30nm thick fullerene or PCBM is deposited at a high speed, and then... The speed of vapor deposition is 7nm to 10nm thick bartoplin or atomic deposition of tin dioxide;
[0035] And / or, prepare a metal electrode layer, specifically including: using The metal is deposited at a high speed until the metal thickness reaches 80nm to 100nm.
[0036] The beneficial effects of the technical solution provided in this application include:
[0037] This application provides an additive-modified perovskite solar cell and its preparation method. In this application, the wide-bandgap perovskite polycrystalline layer is doped with piracetam, an organic compound with amide and hydrophilic structures. During preparation, piracetam is added to the perovskite precursor solution and annealed, which helps to adjust the crystal orientation of the perovskite film. Specifically, the (110) orientation, which is beneficial to the quality of perovskite crystals, is promoted, while the unfavorable (100) orientation is suppressed. This increases the grain size of the perovskite film, reduces non-radiative recombination, and improves the uniformity of the perovskite film. More importantly, a uniform and smooth perovskite film is beneficial for manufacturing more efficient all-perovskite tandem solar cells. Attached Figure Description
[0038] To more clearly illustrate the technical solutions in the embodiments of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0039] Figure 1 A schematic diagram of an additive-modified perovskite solar cell provided in an embodiment of this application;
[0040] Figure 2 This is a SEM image of the wide-bandgap perovskite polycrystalline layer of Comparative Example 1 of this application;
[0041] Figure 3 This is a SEM image of the wide-bandgap perovskite polycrystalline layer of Embodiment 2 of this application;
[0042] Figure 4This is a bar chart showing the grain size distribution of the wide-bandgap perovskite polycrystalline layer in Comparative Example 1 of this application;
[0043] Figure 5 This is a bar chart showing the grain size distribution of the wide-bandgap perovskite polycrystalline layer in Embodiment 2 of this application;
[0044] Figure 6 AFM image of a wide-bandgap perovskite polycrystalline layer in Comparative Example 1 of this application;
[0045] Figure 7 This is an AFM image of a wide-bandgap perovskite polycrystalline layer from Embodiment 2 of this application;
[0046] Figure 8 These are the external quantum efficiency test graphs for Embodiment 2 and Comparative Example 1 of this application;
[0047] Figure 9 Photoelectric conversion efficiency diagrams of wide bandgap devices, narrow bandgap devices, and all-perovskite multilayer devices provided in this application;
[0048] Figure 10 The graphs show the photoelectric conversion efficiency of Embodiment 4 and Comparative Example 2 of this application.
[0049] In the figure: 1. First conductive glass layer; 2. First hole transport layer; 3. Wide bandgap perovskite polycrystalline layer; 4. First electron transport layer; 5. Second conductive glass layer; 6. Second hole transport layer; 7. Narrow bandgap perovskite polycrystalline layer; 8. Second electron transport layer; 9. Metal electrode layer. Detailed Implementation
[0050] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0051] See Figure 1 As shown, this application provides an additive-modified perovskite solar cell, which includes a first conductive glass layer 1, a first hole transport layer 2, a wide-bandgap perovskite polycrystalline layer 3, a first electron transport layer 4, and a metal electrode layer 9 stacked sequentially; wherein, the wide-bandgap perovskite polycrystalline layer 3 is doped with a modifier, the modifier including piracetam.
[0052] In this application, the wide-bandgap perovskite polycrystalline layer is doped with piracetam, an organic compound with amide and hydrophilic structures. During preparation, piracetam is added to the perovskite precursor solution and annealed, which helps to adjust the crystal orientation of the perovskite film. Specifically, the (110) orientation, which is beneficial to the quality of perovskite crystals, is promoted, while the (100) orientation, which is unfavorable, is suppressed. This increases the grain size of the perovskite film, reduces non-radiative recombination, and improves the uniformity of the perovskite film. More importantly, a uniform and smooth perovskite film is beneficial for manufacturing more efficient all-perovskite tandem solar cells.
[0053] In this application, the material of the first conductive glass layer 1 can be selected from various options, depending on the actual fabrication requirements. For example, as an example, the first conductive glass layer 1 is fluorine-doped tin dioxide (FTO). As another example, the first conductive glass layer 1 is indium-doped tin dioxide (ITO).
[0054] In this application, the first hole transport layer 2 includes two hole layers: a lower hole layer located on the first conductive glass layer 1 and an upper hole layer located on the lower hole layer. The lower hole layer uses NiOx, where x is 2 or 3. The upper hole layer uses Me-4PACz (i.e., [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphate) or 2PACz (i.e., [2-(9H-carbazole-9-yl)ethyl]phosphonic acid). Adding Me-4PACz or 2PACz has the advantage of being more conducive to hole transport and improving device performance.
[0055] In this application, the first electron transport layer 4 can be a single layer or a double layer. For example, as an example, the first electron transport layer 4 is a single layer, which can be a fullerene or a fullerene derivative PCBM. As another example, the first electron transport layer 4 includes a lower transport layer located on a wide-bandgap perovskite polycrystalline layer 3 and an upper transport layer located on the lower transport layer. The lower transport layer uses a fullerene or PCBM, and the upper transport layer uses bartoplin or atomically deposited tin dioxide. Adding bartoplin or atomically deposited tin dioxide has the advantage of being more conducive to electron transport and improving device performance.
[0056] This application can also be designed with multiple layers, for example, see [link to relevant documentation] Figure 1 As shown, a second conductive glass layer 5, a second hole transport layer 6, a narrow bandgap perovskite polycrystalline layer 7, and a second electron transport layer 8 are sequentially stacked between the first electron transport layer 4 and the metal electrode layer 9.
[0057] The second conductive glass layer 5 can be a single layer or a double layer. For example, as an example, the second conductive glass layer 5 is a single layer, which can be made of bartoplin or atomically deposited tin dioxide. As another example, the second conductive glass layer 5 includes a lower conductive glass layer and an upper conductive glass layer located on the lower conductive glass layer. The lower conductive glass layer is made of atomically deposited tin dioxide, and the upper conductive glass layer is made of nano-gold or indium-doped tin dioxide. The advantage of adding nano-gold or indium-doped tin dioxide is that it acts as a composite layer, which is beneficial to improving device performance.
[0058] The second hole transport layer 6 is made of poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) or NiOx, where x is 2 or 3.
[0059] The second electron transport layer 8 can be a single layer or a double layer. For example, as an example, the second electron transport layer 8 can be a single layer, which can be made of fullerene or PCBM. As another example, the second electron transport layer 8 includes a lower transport layer located on a narrow bandgap perovskite polycrystalline layer 7 and an upper transport layer located on the lower transport layer. The lower transport layer is made of fullerene or PCBM, and the upper transport layer is made of bartoplin or atomically deposited tin dioxide. Adding bartoplin or atomically deposited tin dioxide has the advantage of being more conducive to electron transport and improving device performance.
[0060] This application also provides a method for preparing an additive-modified perovskite solar cell, which includes the following steps: sequentially preparing a first hole transport layer 2, a wide-bandgap perovskite polycrystalline layer 3, a first electron transport layer 4 and a metal electrode layer 9 on a first conductive glass layer 1 to obtain an additive-modified perovskite solar cell.
[0061] The preparation of the first hole transport layer 2 specifically includes the following steps:
[0062] 101: First, NiOx is mixed and stirred with the first solvent, then spin-coated onto the first conductive glass layer 1, and then subjected to the first annealing treatment to obtain the lower hole layer.
[0063] In step 101, the concentration of NiOx after mixing with the first solvent is 10 mg / ml - 20 mg / ml;
[0064] The first solvent can be deionized water or isopropanol.
[0065] The conditions for the first annealing treatment include: annealing at 110℃~180℃ for 15min~40min; preferably, annealing at 130℃ for 30min.
[0066] The spin coating speed is 3000 rpm to 4000 rpm, and the spin coating time is 25 s to 40 s; preferably, the spin coating speed is 3000 rpm and the spin coating time is 30 s.
[0067] 102: Then mix Me-4PACz or 2PACz with the second solvent and stir, then spin coat it onto the lower cavity layer, and then perform a second annealing treatment to obtain the upper cavity layer.
[0068] In step 102, the concentration of Me-4PACz or 2PACz after mixing with the second solvent is 0.3 mg / ml to 1 mg / ml;
[0069] The second solvent can be ethanol or isopropanol.
[0070] The conditions for the second annealing treatment include: annealing at 100℃~120℃ for 5min~15min; preferably, annealing at 100℃ for 10min.
[0071] The spin coating speed is 3000 rpm to 4000 rpm, and the spin coating time is 25 s to 40 s; preferably, the spin coating speed is 3000 rpm and the spin coating time is 30 s.
[0072] The preparation of the wide-bandgap perovskite polycrystalline layer 3 specifically includes the following steps:
[0073] 201: Formamidinium hydroiodide (FAI), cesium iodide (CsI), lead iodide (PbI2), and lead bromide (PbBr2) are mixed in N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO). After stirring at 50°C to 70°C, piracetam is added and mixed to form a perovskite precursor solution.
[0074] In step 201, the concentration of formamidine hydroiodide (FAI) in the perovskite precursor solution is 0.96 mol / L, the concentration of cesium iodide (CsI) is 0.24 mol / L, the concentration of lead iodide (PbI2) is 0.48 mol / L, the concentration of lead bromide (PbBr2) is 0.72 mol / L, and the concentration of piracetam is less than 5 mg / ml.
[0075] The volume ratio of DMF to DMSO is (3-4):1, preferably 4:1.
[0076] 202: Spin-coat the perovskite precursor liquid onto the first hole transport layer 2, and heat it to form a wide-bandgap perovskite polycrystalline layer 3.
[0077] In step 202, the heating process after spin coating of the perovskite precursor liquid includes: annealing at 55℃~75℃ for 90s~120s, and then annealing at 95℃~105℃ for 10min~15min; preferably, annealing at 65℃ for 120s, and then annealing at 100℃ for 10min.
[0078] The preparation of the first electron transport layer 4 specifically includes: using a vacuum thermal evaporation method, firstly... A 20nm-30nm thick fullerene or PCBM is deposited at a high speed, and then... The process involves vapor deposition of 7nm–10nm thick Bartoplin or atomically deposited tin dioxide at a high speed; preferably, vacuum thermal evaporation is used, first... A 20nm thick layer of fullerene is deposited at a high speed, and then... The speed of vapor deposition of 7nm thick bartoprin.
[0079] The preparation of the metal electrode layer 9 specifically includes: using The metal is deposited at a rate of [speed] until the metal thickness reaches 80 nm to 100 nm; preferably, at [speed]. The metal is deposited at a high speed until the metal thickness reaches 100nm.
[0080] Comparative Example 1:
[0081] A perovskite solar cell includes a conductive glass layer, a hole transport layer, a perovskite polycrystalline layer, an electron transport layer, and a metal electrode layer stacked sequentially.
[0082] The fabrication method of perovskite solar cells is as follows:
[0083] Step S1: Clean and dry the 2cm×2cm first conductive glass layer 1 (material is ITO).
[0084] Step S2: Mix 10 mg of nickel oxide with 1 ml of deionized water and stir. Spin-coat the mixture onto the first conductive glass layer 1 at 3000 rpm for 30 s. Anneal at 130 °C for 30 min. After cooling, transfer to a glove box to obtain the lower hole layer. Then, mix 0.3 mg of [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphoric acid with 1 ml of ethanol and stir. Spin-coat the mixture onto the lower hole layer at 3000 rpm for 30 s. Anneal at 100 °C for 10 min to form the upper hole layer. The lower hole layer and the upper hole layer together constitute the first hole transport layer 2.
[0085] Step S3: CsI, FAI, PbI2 and PbBr2 are mixed in DMF and DMSO to form a perovskite precursor solution, wherein the concentration of CsI is 0.24 mol / L, the concentration of FAI is 0.96 mol / L, the concentration of PbI2 is 0.48 mol / L, the concentration of PbBr2 is 0.72 mol / L, and the volume ratio of DMF to DMSO is 4:1. The perovskite precursor solution is stirred at 70°C for 2 hours. 40 μL of the perovskite precursor solution is taken out and applied to the first hole transport layer 2. It is first spin-coated at 1000 rpm for 5 seconds, then spin-coated at 5000 rpm for 30 seconds, and then annealed at 65°C for 120 seconds and 100°C for 10 minutes respectively to form a wide-bandgap perovskite polycrystalline layer 3.
[0086] Step S4: with Fullerene C is sequentially deposited on the surface of the wide-bandgap perovskite polycrystalline layer 3 at a certain speed. 60 The first electron transport layer 4 was fabricated using bartoplin BCP with thicknesses of 20 nm and 7 nm, respectively.
[0087] Step S5: with Cu is deposited on the surface of the electron transport layer at a rate of 100 nm until the Cu thickness reaches 100 nm, thus completing the preparation of the metal electrode layer 9.
[0088] Example 1:
[0089] The difference between this embodiment and Comparative Example 1 is that in step S3, after the perovskite precursor solution is stirred, piracetam is added first, and then the solution is shaken manually several times. Since piracetam has good miscibility with both DMF and DMSO, it can be quickly and evenly dispersed in DMF and DMSO, thus ensuring that piracetam does not affect the crystallinity of the perovskite.
[0090] In this embodiment, the concentration of piracetam in the perovskite precursor solution is 1 mg / ml.
[0091] In step S3 of this embodiment, during the annealing process at 65°C for 120 seconds, the C=O in piracetam may react with Pb. 2+ Coordination bonds are formed between them, which suppresses the (100) orientation that is not conducive to crystal growth and enhances the (110) orientation that is conducive to the quality of perovskite crystals, thereby improving the quality and uniformity of the film and making it more conducive to the preparation of large-area perovskites.
[0092] Example 2:
[0093] The difference between this embodiment and Example 1 is that the concentration of piracetam in the perovskite precursor solution is 3 mg / ml.
[0094] Example 3:
[0095] The difference between this embodiment and Example 1 is that the concentration of piracetam in the perovskite precursor solution is 5 mg / ml.
[0096] Table 1
[0097]
[0098] The photoelectric parameters of the batteries in Comparative Example 1 and Examples 1 to 3 are shown in Table 1. The test conditions were AM1.5G and light intensity of 100mW / cm². 2 .
[0099] As can be seen, with the increase of piracetam doping concentration, the open-circuit voltage, current density, and fill factor all increase to a certain extent, resulting in a significant increase in cell efficiency, until the piracetam doping concentration reaches 3 mg / mL. However, when the piracetam doping concentration rises to 5 mg / mL, the open-circuit voltage, current density, and fill factor all decrease to varying degrees, directly leading to a decrease in cell efficiency. This is because excessive piracetam may be detrimental to the crystallization quality of the perovskite.
[0100] See Figure 2 , Figure 3 , Figure 4 , Figure 5 , Figure 6 and Figure 7 As can be seen, with the addition of piracetam to perovskite, the grain size increases significantly, with the average grain size increasing from 0.29 μm to 0.96 μm, and the surface roughness decreasing from 28.6 nm to 17.2 nm. This demonstrates that piracetam significantly improves the crystallization effect of perovskite.
[0101] Between Example 2 and Comparative Example 1, the increase in current density was not significant. To demonstrate the effect of piracetam on improving short-circuit current density and to eliminate experimental error interference, the external quantum efficiency of the solar cell was tested. See [link to relevant documentation]. Figure 8 The external quantum efficiency of solar cells in the 380nm–700nm range shows a significant improvement. In Example 2, by doping with piracetam, the integrated current density increased from 17.93 mA / cm². 2 Increased to 18.25 mA / cm 2 This demonstrates the effect of piracetam on increasing current density.
[0102] It is worth noting that piracetam also significantly improves the efficiency of tandem solar cell devices.
[0103] Fabrication process of all-perovskite multilayer devices: See Figure 1 and Figure 9As shown, in step S4 of Comparative Example 1, fullerene C was deposited on the surface of the wide-bandgap perovskite polycrystalline layer 3. 60 Subsequently, instead of evaporating bartoplin BCP, atomic deposition of tin dioxide and gold nanoparticles was performed sequentially to form the second conductive glass layer 5. Then, poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) was deposited to form the second hole transport layer 6. Next, a narrow-bandgap perovskite polycrystalline layer 7 was deposited, followed by the sequential deposition of fullerene C. 60 The second electron transport layer 8 is formed by combining the bartoplin BCP and the metal electrode layer 9 in step S5, and then the all-perovskite stacked device is obtained.
[0104] Specifically, the preparation of the second conductive glass layer 5 includes: firstly, using atomic layer deposition, depositing a layer of conductive glass using atomic layer deposition... Tin dioxide with a deposition rate of 18nm–22nm was deposited, and then... Gold nanometers of 0.8 nm to 1 nm can be deposited at high speeds.
[0105] The preparation of the second hole transport layer 6 specifically includes: diluting (3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) with deionized water or ethanol at a volume ratio of 1:1 or 3:1, followed by spin coating. Then, annealing is performed at 130℃~150℃ for 30min~40min. The spin coating speed is 5000rpm~6000rpm, and the spin coating time is 30s~40s.
[0106] The preparation of the narrow bandgap perovskite polycrystalline layer 7 specifically includes: mixing formamidinium hydroiodate (FAI), methylamine hydroiodate (MAI), lead iodide (PbI2), and stannous iodide (SnI2) in N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), stirring and heating at 25℃~30℃ for 1~2h to form a perovskite precursor solution. In the perovskite precursor solution, the concentration of formamidinium hydroiodate (FAI) is 1.47 mol / L, the concentration of methylamine hydroiodate (MAI) is 0.63 mol / L, the concentration of lead iodide (PbI2) is 1.05 mol / L, the concentration of stannous iodide (SnI2) is 1.05 mol / L, and the volume ratio of DMF to DMSO is 3:1; spin-coating the perovskite precursor solution onto the second hole transport layer 6 and heating it. The heating process includes: directly annealing at 100℃~110℃ for 10min~15min.
[0107] The preparation of the second electron transport layer 8 specifically includes: using a vacuum thermal evaporation method, firstly... Fullerenes with a wavelength of 20nm to 25nm were deposited at a high speed, and then... The speed of vapor deposition of 7nm of bartoprin.
[0108] The perovskite solar cell of Example 2 was used as a wide bandgap device.
[0109] The fabrication process for narrow bandgap devices is as follows: Referring to the fabrication process for all-perovskite stacked devices, in step S1 of Comparative Example 1, poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) is directly deposited to form the second hole transport layer 6, followed by the deposition of a narrow bandgap perovskite polycrystalline layer 7, and then the deposition of fullerene C. 60 The second electron transport layer 8 is formed by combining the bartoplin BCP and the metal electrode layer 9 in step S5, and then the narrow bandgap device is obtained.
[0110] Thanks to the enhancement effect of piracetam on perovskite devices, the photoelectric conversion efficiency of the all-perovskite tandem device reached an astonishing 28.23%. The photoelectric parameters of the wide bandgap, narrow bandgap, and tandem device cells are shown in Table 2.
[0111] Table 2
[0112]
[0113] In this application, piracetam-doped perovskite precursor solution was used to suppress the (100) orientation, which is detrimental to crystal quality, and promote the (110) orientation, which is beneficial to crystal quality. This resulted in a significant reduction in overall defects in the perovskite film, a significant increase in grain size, and a substantial improvement in uniformity and photostability. Based on this, a 1.77 eV bandgap perovskite solar cell FA was prepared in Example 2. 0.8 Cs 0.2 Pb(I 0.6 Br 0.4 )3, achieving a photoelectric conversion efficiency of 20.12% and an open-circuit voltage of 1.34V.
[0114] Meanwhile, based on this, a fully perovskite tandem solar cell with a photoelectric conversion efficiency of 28.23% was also prepared.
[0115] It should be noted that the advantages of this application are illustrated above using a perovskite solar cell with a bandgap of 1.77 eV as an example. In fact, this application is not only applicable to wide bandgap perovskites of 1.77 eV, but also to other bandgap perovskites.
[0116] For example, referring to the preparation method of Example 2, a perovskite solar cell FA with a bandgap of 1.56 eV was re-prepared using piracetam. 0.9 MA 0.05 Cs 0.05 Pb(I 0.95 Br 0.05 Example 3 was used as Example 4. Meanwhile, referring to the preparation method of Comparative Example 1, the prepared perovskite solar cell was used as the control group of Example 4 and was recorded as Comparative Example 2.
[0117] See Figure 10 In Example 4, the addition of piracetam significantly improved the photoelectric conversion efficiency, from 22.75% to 24.91%. The photoelectric parameters of the device battery are shown in Table 3.
[0118] Table 3
[0119]
[0120] The above description is merely a specific embodiment of this application, enabling those skilled in the art to understand or implement this application. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of this application. Therefore, this application is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features claimed herein.
Claims
1. A method for preparing an additive-modified perovskite solar cell, characterized in that, It includes the following steps: A first hole transport layer (2), a wide-bandgap perovskite polycrystalline layer (3), a first electron transport layer (4), a second conductive glass layer (5), a second hole transport layer (6), a narrow-bandgap perovskite polycrystalline layer (7), a second electron transport layer (8), and a metal electrode layer (9) are sequentially prepared on a first conductive glass layer (1). The wide-bandgap perovskite polycrystalline layer (3) is doped with a modifier, the modifier of which includes piracetam, to obtain an additive-modified perovskite solar cell. In this process, the perovskite precursor solution is spin-coated onto the first hole transport layer (2), and after heating, a wide-bandgap perovskite polycrystalline layer (3) is formed. The concentration of piracetam in the perovskite precursor solution is 1 mg / mL to 5 mg / mL.
2. The method for preparing the additive-modified perovskite solar cell as described in claim 1, characterized in that, The preparation of the first hole transport layer (2) specifically includes: First, NiOx is mixed and stirred with the first solvent, then spin-coated onto the first conductive glass layer (1), and then subjected to the first annealing treatment to obtain the lower hole layer, where x takes the value of 2 or 3; Then, Me-4PACz or 2PACz is mixed and stirred with the second solvent, then spin-coated onto the lower cavity layer, followed by a second annealing treatment to obtain the upper cavity layer.
3. The method for preparing the additive-modified perovskite solar cell as described in claim 2, characterized in that: The concentration of NiOx after mixing with the first solvent is 10 mg / ml-20 mg / ml; And / or, the concentration of Me-4PACz or 2PACz after mixing with the second solvent is 0.3 mg / ml-1 mg / ml; And / or, the first solvent is deionized water or isopropanol; And / or, the conditions for the first annealing treatment include: annealing at 110℃~180℃ for 15min~40min; And / or, the spin coating speed is 3000 rpm to 4000 rpm, and the spin coating time is 25 s to 40 s; And / or, the second solvent is ethanol or isopropanol; And / or, the conditions for the second annealing treatment include: annealing at 100℃~120℃ for 5min~15min.
4. The method for preparing the additive-modified perovskite solar cell as described in claim 1, characterized in that: Formamidin hydroiodide (FAI), cesium iodide (CsI), lead iodide (PbI2), and lead bromide (PbBr2) were mixed in N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), and then piracetam was added after stirring to form a perovskite precursor solution.
5. The method for preparing the additive-modified perovskite solar cell as described in claim 4, characterized in that: In the perovskite precursor solution, the concentrations of formamidine hydroiodate (FAI) were 0.96 mol / L, cesium iodide (CsI) were 0.24 mol / L, lead iodide (PbI2) were 0.48 mol / L, and lead bromide (PbBr2) were 0.72 mol / L. And / or, the volume ratio of DMF to DMSO is (3-4):1; And / or, stir at 50℃~70℃; And / or, the heating process after spin-coating the perovskite precursor solution includes: first annealing at 55℃~75℃ for 90s~120s, and then annealing at 95℃~105℃ for 10min~15min.
6. The method for preparing the additive-modified perovskite solar cell as described in claim 1, characterized in that: The preparation of the first electron transport layer (4) specifically includes: first, by vacuum thermal evaporation, depositing a fullerene or PCBM with a thickness of 20 nm to 30 nm at a speed of 0.05 Å / s to 0.15 Å / s, and then depositing a bartoplin or atomically deposited tin dioxide with a thickness of 7 nm to 10 nm at a speed of 0.05 Å / s to 0.1 Å / s. And / or, prepare a metal electrode layer (9), specifically including: evaporating metal at a rate of 0.4 Å / s to 0.7 Å / s until the metal thickness reaches 80 nm to 100 nm.
7. A perovskite solar cell modified with additives, characterized in that, The perovskite solar cell was prepared using the additive-modified method described in claim 1.
8. The perovskite solar cell modified with additives as described in claim 7, characterized in that: The first conductive glass layer (1) is fluorine-doped tin dioxide or indium-doped tin dioxide; And / or, the first hole transport layer (2) includes a lower hole layer and an upper hole layer located on the lower hole layer, wherein the lower hole layer is made of NiOx, x is 2 or 3, and the upper hole layer is made of Me-4PACz or 2PACz. And / or, the first electron transport layer (4) is made of fullerene or PCBM, or the first electron transport layer (4) includes a lower transport layer and an upper transport layer located on the lower transport layer, wherein the lower transport layer is made of fullerene or PCBM and the upper transport layer is made of bartoplin or atomically deposited tin dioxide.
9. The perovskite solar cell modified with additives as described in claim 1, characterized in that: The second conductive glass layer (5) is made of bartoplin or atomically deposited tin dioxide, or the second conductive glass layer (5) includes a lower conductive glass layer and an upper conductive glass layer located on the lower conductive glass layer, wherein the lower conductive glass layer is made of atomically deposited tin dioxide and the upper conductive glass layer is made of nano-gold or indium-doped tin dioxide; And / or, the second hole transport layer (6) is made of poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) or NiOx, where x is 2 or 3; And / or, the second electron transport layer (8) is made of fullerene or PCBM, or the second electron transport layer (8) includes a lower transport layer and an upper transport layer located on the lower transport layer, the lower transport layer being made of fullerene or PCBM, and the upper transport layer being made of bartoplin or atomically deposited tin dioxide.
Citation Information
Patent Citations
Perovskite solar cell devive and manufacturing method thereof
KR1020220126668A
Preparation method for organic-inorganic hybrid perovskite thin film and preparation method for semi-transparent solar cell
WO2023184626A1